2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Right-to-Know Law [State]: FE413, 7/2003 - Polopolus, Leo C.; Olexa, Michael T.; Roka, Fritz; Fountain, Carol (EDIS, 2003)
The Right-to-Know Law establishes Florida standards of safety for certain employers who manufacture, produce, use, apply, or store toxic substances. This is EDIS document FE413, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers. FE413/FE413: 2017 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Right-to-Know Law [State] (ufl.edu)